Music Syncing as Intermedial Translation (Sound Stage Screen, 2023)
In this article I discuss the notion of intermedial translation in the context of audiovisual works. I begin by presenting Lars Elleström’s modality model as it provides the larger framework under which I then specify the scope of intermedial translation. After confronting different interpretation of the concept, I present my main contribution, which links this theoretical notion to the practice of music synchronization. I argue that the resulting approach provides a unique tool for the analysis of audiovisual artefacts. In order to further clarify this analytical perspective and prove its usefulness, I then proceed to apply it to artifacts created through a variety of software, ranging from music visualizers to video games. A look into 2006 Flash game Line Rider and the online community that spawned around it completes the article as my main case study.
Keywords: intermediality; intermedial translation; animation; music syncing; casual creators